Guinea : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Guinea. (IMF Staff Country Reports; Country Report ;, 2021)
While the non-mining sector was severely impacted by the COVID-19 crisis, overall growth in Guinea remains strong, reaching 7 percent in 2020, driven by booming mining production. Inflation exceeded 12 percent as a result of COVID-related supply disruptions and the ongoing monetary and fiscal response. The already weak social indicators have deteriorated further.